LAST SURVIVOR INSURANCE PREMIUM USING ASYMMETRIC COPULA MODEL WITH MAKEHAM DEATH ASSUMPTION - S. Imran, Rusniwati
Last survivor life insurance is combined life insurance (multiple life). Premium payments for last survivor life insurance are made until both insured persons die, and at that time compensation is paid from the insurer. The insured's risk of death, expressed in the probability of death, has an influence in calculating the annual premium. The assumption of freedom between insureds affects the premium amount. However, in reality, the life of a husband and wife has shared risks with two possibilities that the effect of the husband's death on the wife can be different from the effect of the wife's death on the husband which is called asymmetric. This research calculates the annual premium for m-year term life insurance for last survivor status with the assumption of asymmetric mortality independence using the Generalized Farlie Gumbel-Morgenstern (GFGM) Type-II copula model, and the survival function uses the Makeham mortality assumption. Age data for husband and wife couples uses the Indonesian Mortality Table IV 2019 which differentiates between male and female gender. Couples' ages were grouped into 3, namely young couples (26-40), quite old (41-55), and elderly couples (56-70). The results of premium calculations for the three groups of couples are that elderly couples have the largest premiums compared to premiums for young and quite old couples. The greater the size of the life dependency (????) of a husband and wife, the greater the premium that should be paid. Therefore, the premium amount is influenced by the size of the dependency and the age of the husband and wife.